1998
DOI: 10.1145/280277.280278
|View full text |Cite
|
Sign up to set email alerts
|

Models and languages for parallel computation

Abstract: We survey parallel programming models and languages using six criteria to assess their suitability for realistic portable parallel programming. We argue that an ideal model should by easy to program, should have a software development methodology, should be architecture-independent, should be easy to understand, should guarantee performance, and should provide accurate information about the cost of programs. These criteria reflect our belief that developments in parallelism must be driven by a parallel softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
9

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(109 citation statements)
references
References 66 publications
0
98
0
9
Order By: Relevance
“…In practice, it is certainly possible to implement BSP programs using the traditional PVM [55] and MPI [45] libraries. A number of studies have shown that bulk-synchronous parallel algorithms lead to more efficient performance than their message-passing or shared-memory counterparts in many applications [61,62].…”
Section: Bsp and The Cost Modelmentioning
confidence: 99%
“…In practice, it is certainly possible to implement BSP programs using the traditional PVM [55] and MPI [45] libraries. A number of studies have shown that bulk-synchronous parallel algorithms lead to more efficient performance than their message-passing or shared-memory counterparts in many applications [61,62].…”
Section: Bsp and The Cost Modelmentioning
confidence: 99%
“…To identify concepts, we rely foremost on the overview given by two surveys [2,25] as our main subjects. They give a broad foundation but are dated.…”
Section: Selecting Subjects and Identifying Conceptsmentioning
confidence: 99%
“…Our survey is based on two surveys [2,25] and thus closely related to them. However, we are not aware on any survey or approach that enables a runtime system to directly support the semantics of multiple concurrency models.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the description of the application should be at the correct abstraction level to perform the required analysis [KNRSV00]. A comprehensive survey of models for parallel computations used in different application domains and at different abstraction levels is given in [ST98]. The most interesting models for our application domain, streaming multimedia systems, are the dataflow models.…”
Section: Related Workmentioning
confidence: 99%